Cross-species transcriptomes reveal species-specific and shared molecular adaptations for plants development on iron-rich rocky outcrops soils - Dias, Mariana Costa; Caldeira, Cecílio; Gastauer, Markus; Ramos, Silvio; Oliveira, Guilherme (BMC genomics, 2022)
Canga is the Brazilian term for the savanna-like vegetation harboring several endemic species on iron-rich rocky outcrops, usually considered for mining activities. Parkia platycephala Benth. and Stryphnodendron pulcherrimum (Willd.) Hochr. naturally occur in the cangas of Serra dos Carajás (eastern Amazonia, Brazil) and the surrounding forest, indicating high phenotypic plasticity. The morphological and physiological mechanisms of the plants' establishment in the canga environment are well studied, but the molecular adaptative responses are still unknown. To understand these adaptative responses, we aimed to identify molecular mechanisms that allow the establishment of these plants in the canga environment. Plants were grown in canga and forest substrates collected in the Carajás Mineral Province. RNA was extracted from pooled leaf tissue, and RNA-seq paired-end reads were assembled into representative transcriptomes for P. platycephala and S. pulcherrimum containing 31,728 and 31,311 primary transcripts, respectively. We identified both species-specific and core molecular responses in plants grown in the canga substrate using differential expression analyses. In the species-specific analysis, we identified 1,112 and 838 differentially expressed genes for P. platycephala and S. pulcherrimum, respectively. Enrichment analyses showed that unique biological processes and metabolic pathways were affected for each species. Comparative differential expression analysis was based on shared single-copy orthologs. The overall pattern of ortholog expression was species-specific. Even so, we identified almost 300 altered genes between plants in canga and forest substrates with conserved responses in the two species. The genes were functionally associated with the response to light stimulus and the circadian rhythm pathway. Plants possess species-specific adaptative responses to cope with the substrates. Our results also suggest that plants adapted to both canga and forest environments can adjust the circadian rhythm in a substrate-dependent manner. The circadian clock gene modulation might be a central mechanism regulating the plants' development in the canga substrate in the studied legume species. The mechanism may be shared as a common mechanism to abiotic stress compensation in other native species.